2020
DOI: 10.1016/j.ast.2020.106179
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady aerodynamics analysis and modelling of a Slingsby Firefly aircraft: Detached-Eddy Simulation model and flight test validation

Abstract: This paper presents unsteady stall characteristics of a Slingsby T67M260 Firefly light aircraft from both a computational fluid dynamics (CFD) half model and flight tests. Initial results from the steady CFD, based on a RANS k − ω SST turbulence model, established the critical angle of attack of the stall to be α stall = 16 • , with a maximum lift coefficient of CLmax = 1.2. Comparisons with straight and level flight test data were comparable up to α = 12 • -14 • , with the increasing deviation at higher α att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Around 1.5s later, the aircraft is stalled and the dominant frequencies switch from the engine to the aerodynamic and structural interactions, indicated in Figure2b, where the tailplane structural natural frequencies are excited at 9.4Hz and 40.5Hz. In this case, the DES model was predicting aerodynamic wake shedding frequencies close to the lower frequency of the tailplane structure(Neves et al 2020), as confirmed by the video footage of the tail. In the last two stages of the sequence, a large change and reduction in acceleration can be seen which coincides with the 'wing drop' in a heavy stall.…”
supporting
confidence: 62%
See 4 more Smart Citations
“…Around 1.5s later, the aircraft is stalled and the dominant frequencies switch from the engine to the aerodynamic and structural interactions, indicated in Figure2b, where the tailplane structural natural frequencies are excited at 9.4Hz and 40.5Hz. In this case, the DES model was predicting aerodynamic wake shedding frequencies close to the lower frequency of the tailplane structure(Neves et al 2020), as confirmed by the video footage of the tail. In the last two stages of the sequence, a large change and reduction in acceleration can be seen which coincides with the 'wing drop' in a heavy stall.…”
supporting
confidence: 62%
“…Previous work by the authors described the DES model based on k − ω SST formulation, and its application in modelling the unsteady flow field around the Slingsby in the stalled condition (Neves et al 2020). The following section summarises the main details of the CFD simulation and outlines the additional data extracted from the computed unsteady flow field, to apply the proper orthogonal decomposition (POD) and HODMD methods to the DES wake data.…”
Section: Cfd Modellingmentioning
confidence: 99%
See 3 more Smart Citations